Promosi Wisata Lembah Harau - Helga Akhyar; Eko Purnomo (Journal on Education, 2023)
Harau Valley is located in Harau District, Fifty Cities District, West Sumatra. This area has quite a variety of natural beauty, such as waterfalls and forests. Promotional efforts for the Harau Valley tourism have been carried out but have not been effective. For this reason, development is needed by designing a promotional media video in the form of audio and visual tourist objects. This design uses the 4D method which consists of Define, Design, Development, and Dissemination. With the result of being a promotional video as the main media in the form of cinematic videos, of course the public will know visually about various tourist attractions in the Harau Valley, so that the wider community feels interested in visiting and generates curiosity because it displays a different atmosphere in the video and the visuals displayed are expected will make the public or audience amazed at the tourist attractions in the Harau Valley